Catalytic Cracking of Iraqi Vacuum Gasoil Using Large and Medium Pore Size of Zeolite Catalysts - Rahman, Ameel Mohammed; Salman, Mohanned H.; Hammed, Khalid Waleed (Al-Khwarizmi Engineering Journal, 2014)
Abstract The catalytic cracking conversion of Iraqi vacuum gas oil was studied on large and medium pore size (HY, HX, ZSM-22 and ZSM-11) of zeolite catalysts. These catalysts were prepared locally and used in the present work. The catalytic conversion performed on a continuous fixed-bed laboratory reaction unit. Experiments were performed in the temperature range of 673 to 823K, pressure range of 3 to 15bar, and LHSV range of 0.5-3h-1. The results show that the catalytic conversion of vacuum gas oil increases with increase in reaction temperature and decreases with increase in LHSV. The catalytic activity for the proposed catalysts arranged in the following order: HY>HX>ZSM-11>ZSM-22 The product distribution depends greatly on the temperature and on the catalyst type. A higher hydrocarbon yields was obtained for HY zeolite catalyst. The selectivity towards high octane number compounds for the proposed catalysts are arranged in the following order: HY>HX>ZSM-11>ZSM-22The cracking conversion is improved by increasing reaction pressure up to 15 bar. The simulated experiments of the catalytic cracking process show that the higher conversion and more desired products can be achieved to conventional feeds. Keywords: catalytic cracking, vacuum gas oil, Zeolite, HY, HX, ZSM-11, ZSM-22.